(untitled) (Journal of the College of Languages (JCL), 2012)
In this paper , some of lexical stylistic , syntactical stylistic devices , and one phonetic stylistic device are going to be illustrated in the study of the aphorisms of “life and death” . These stylistic devices are parallelism , hyperbole , alliteration , meiosis , irony , oxymoron , cliché , litotes , metalepsis , and loose sentences. This paper aims at identifying the functions and the frequencies of these devices. These stylistic devices make one speech and writing more interesting and help to get the attention of readers/ listeners